Meet the Expert : Jim Kalbach on New Directions in Mapping Experiences - Kalbach, James; Kalbach, James (O'Reilly Media, Inc., 2021)
Over the past decade, mapping experiences--a design and marketing technique that attempts to capture an experience in a diagram--has entered the mainstream. Stakeholders are now asking for things like customer journey maps by name, even if they don't know exactly what they're requesting. To keep up with demand, the field, along with associated areas such as experience design, service design, and customer experience management, is maturing quickly, bringing with it a number of necessary changes. Join us for this edition of Meet the Expert with Jim Kalbach. You'll get an overview of experience mapping fundamentals and explore five trends shaping the field today: facilitation as a core part of mapping, increased focus on multichannel experiences, the rise of mapping as a management activity, the inclusion of employee experience, and the application of experience mapping outside of commercial settings. What you'll learn and how you can apply it By the end of this live show, you'll better understand: Core concepts in mapping experiences Key trends and changes to the field The future outlook and where the field might be heading This course is for you because ... You want to learn about the fundamental shifts that are transforming the business landscape and customer needs. You want to stay current in new skills related to customer journey mapping, service blueprinting, and similar techniques. Recommended follow-up: Read Mapping Experiences, second edition (book), especially chapter 11," Customer Journey Maps " Read Rapid Techniques for Mapping Experiences (report)